"I would prefer not to": Assessing competence to consent in a case of refusal of cancer treatment. (March 2019) - Castellana, Gustavo B; Schraiber, Lilia B; de Oliveira, Talita R; de Barros, Daniel M
Background: Based on an actual case in which a psychiatrist was called in to assess a patient's capacity to refuse treatment, the aim of this study is to discuss how to manage this ethical and clinical issue and the dilemmas faced by the medical team. Case presentation: The case involved a 45-year-old female patient diagnosed with breast cancer who refused treatment. Since the mastology team had doubts about the patient's mental state and given that she refused to consent to surgery, a forensic psychiatric consult was requested. Conclusion: The forensic psychiatry team concluded that the patient's decision-making capacity was preserved. The team suggested some actions to help the specialists deal with the ethical conflict. A reflection is proposed about the role of psychiatrists when an ethical dilemma involving decision-making capacity emerges in clinical situations, elucidating their work not only as physicians who determine diagnoses and conducts, but also as agents of transformation in the doctor–patient relationship.